2015
DOI: 10.1130/g36688.1
|View full text |Cite
|
Sign up to set email alerts
|

A unique isotopic fingerprint of sulfate-driven anaerobic oxidation of methane

Abstract: The largest reservoir of the powerful greenhouse gas methane is in marine sediments, and catastrophic release of this methane has been invoked to explain climate perturbations throughout Earth history. Marine methane oxidation is mainly coupled anaerobically to microbial sulfate reduction, which both limits and controls the release of methane from this sedimentary reservoir to the rest of Earth's surface. Methane can be transported within the pore space of marine sediments either via diffusion or as bubbles. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 35 publications
5
43
1
Order By: Relevance
“…Previous studies reported that sulfur-cycling AOM can induce sulfur isotope fractionation in marine environments and at sulfate concentrations in the millimolar range Antler et al, 2014Antler et al, , 2015Avrahamov et al, 2014;Deusner et al, 2014;Sivan et al, 2014). A few of these studies assigned ε AOM values of 20-30 for AOM in gas seeps (Deusner et al, 2014;Sivan et al, 2014) and suggested that AOM may cause fractionations of up to 60 in marine SMTZs Deusner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that sulfur-cycling AOM can induce sulfur isotope fractionation in marine environments and at sulfate concentrations in the millimolar range Antler et al, 2014Antler et al, , 2015Avrahamov et al, 2014;Deusner et al, 2014;Sivan et al, 2014). A few of these studies assigned ε AOM values of 20-30 for AOM in gas seeps (Deusner et al, 2014;Sivan et al, 2014) and suggested that AOM may cause fractionations of up to 60 in marine SMTZs Deusner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that sulfurcycling AOM impacts not only sulfur (δ 34 S SO4 ), but also oxygen isotopes (δ 18 O SO4 ) in the dissolved sulfate pool and apparently creates an unique pattern among them that can help to distinguish between organotrophic and methanotrophic SR to be the main drivers of the footprints (e.g., Antler et al, 2014Antler et al, , 2015Avrahamov et al, 2014;Deusner et al, 2014). Therefore, future studies may probably be best approached by combined investigations of oxygen and sulfur isotopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During interglacials, sulfate reduction is confined to the sediments (as it is today), and the rate derived from the δ 18 O (SO4) vs. δ 34 S crossplot suggests the rate of microbial sulfate reduction is faster relative to glacial stages. This could be because of the presence of methane, and that sulfate may be dominantly reduced through anaerobic methane oxidation, associated with a low, unique slope (∼0.39; Antler et al, 2015). This fast rate of microbial sulfate reduction will also contribute to the higher overall sulfur isotope composition of the sedimentary sulfide FIGURE 10 | Conceptual evolution patterns of the Dead Sea lacustrine system across Glacial-Interglacial cycles.…”
Section: The Microbial Sulfur Cycle In Lake Lisanmentioning
confidence: 99%
“…Note that the Masada M1 section of the Lisan Formation, corresponds to depths of ∼177-90 mblf in the DSDDP core. Bottrell and Newton, 2006;Leavitt et al, 2013;Antler et al, 2015).…”
Section: Sulfur and Sulfate Bound Oxygenmentioning
confidence: 99%